Screening of microorganisms for biodegradation of poly(lactic-acid) and lactic acid-containing polymers. - Torres, A (1996)
The ability of some microorganisms to use lactic acid stereocopolymers and copolymers with glycolic acid as sole carbon and energy sources was studied under controlled or natural conditions. First, 14 filamentous fungal strains were tested in liquid cultures, adopting total lactic acid consumption, nitrogen source exhaustion, and maximal biomass production as selection criteria. Two strains of Fusarium moniliforme and one strain of Penicillium roqueforti were able to totally assimilate DL-lactic acid, partially soluble racemic oligomers (MW = 1,000), and the nitrogen source. Only one strain of F. moniliforme was able to grow on a poly(lactic acid)-glycolic acid copolymer (MW = 150,000) after 2 months of incubation at 28 degrees C on synthetic agar medium. Mycelium development was examined by scanning electron microscopy. F. moniliforme filaments were observed to grow not only at the copolymer surface but also through the bulk of the copolymer. In a second approach, plates made of a racemic poly(lactic acid) were buried in the soil before being incubated in petri dishes containing mineral agar medium under controlled conditions. Five strains of different filamentous fungi were isolated, and their ability to assimilate racemic poly(lactic acid) oligomers was tested in liquid cultures.